Managing Salinity in Florida Citrus - Brian J. Boman; Eddie W. Stover (EDIS)
This is document No. AE171 and Circular 1411, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.